Investigation Of Open Green Recreation Spaces’ In Urban Environment With The Context Of Healthy City Planning: Case Of Turkey - Yeliz Ilgar (European Scientific Journal, ESJ, 2016)
The importance of the open-green spaces, the indicator of civilization and standard of urban life has been gradually increasing in recent years. In this context, Turkey has been living through this fast urbanization process by significant changes of its social, economical, ecological and cultural structure from 1950s until today. The fast urbanization in Turkey, has especially brought some important changes in social and cultural life of the urban and increased the needs of recreation and green areas. The aim of this study is to analyze urban open spaces planning process and applications in Turkey from the point of view of healthy city planning. For this reason firstly we tried to analyze legal and practice dimensions of green-open urban spaces in Turkey. As the average amount of the active open-green spaces are less than 10 square meters per capita of the healthy cities in Turkey, the planned areas such as playgrounds and gardens for kids, urban parks of Turkey cities in the terms of quality and quantity are inadequate to meet the recreational needs of the inhabitants. It will be possible that city has a healthy, green and modern urban by means of a process to be put into designing, planning and management by taking into consideration the ecological, scientifically, and technical criteria for raising the quality and quantity of the open-green spaces of the urban.